Integrating Arabic Culture into Arabic Language Learning in the Digital Age: A Study of Generation Z Muslims - Zuhriyah, Lailatul; Shofa, Zahra Nurus; Dzakiyah, Husna (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2025)
As Generation Z emerges as digital natives, it is necessary to update learning methods to be relevant and utilize the digital technologies that are part of their lives. How is Arabic culture active in the realm of Arabic language learning? The method used in this research is descriptive qualitative with a literature study approach. Data were collected from secondary sources such as scientific publications, digital Arabic learning materials, and relevant previous research reports, without directly involving participants. The results show that Generation Z considers cultural learning through social media platforms such as Instagram, TikTok, and YouTube more authentic and contextual than conventional teaching materials such as textbooks. Using news accounts, educational content, videos, and interaction in digital forums is a common practice. The findings imply a shift in the role of educators from the primary source of knowledge to content curators and facilitators of cross-cultural discussions. Consequently, there is an urgent need to develop hybrid teaching materials that integrate the richness of classical content with the relevance of contemporary media to create more effective learning.